What proportion of children stay in the same location as adults, and how does this vary across location and groups? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2009)
This paper provides new information on what proportion of individuals spend their adult work lives in their childhood metropolitan area or state. I also examine how this proportion varies across different demographic groups, and with the size and growth rate of the metropolitan area. I find that the proportion of individuals who spend most of their adulthood in their childhood metropolitan area is surprisingly high. Furthermore, this proportion does not go down as much as one might think for smaller or slower-growing metropolitan areas, or for collegeeducated persons. These findings imply that state and local investments in children may pay off for the state or local area that makes these investments. A surprisingly large proportion of the individuals who benefit from these childhood investments will remain in the same state or local area as adults, thereby boosting the local economy.
Keywords: R23; J61; R28; R11; 330